Development of Health Educational Game Application â€œWorm Freeâ€ Based on Android - Guspianto, Guspianto; Humaryanto; Yun Nina , Ekawati; Mohamad , Ilhami; Shabira, Diyank (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
Background: Strategies for preventing and controlling worms are carried out by increasing PHBS behavior from an early age. Health promotion efforts such as health education for student have been carried out, one of which was through the game method (gamification) which was able to stimulate various senses, attract and be liked by children. In line with the development of communication and information technology, digital-based educational models were very necessary and helpful in improving children's thinking patterns, creativity, and ability to obtain health information. This study aims to develop a digital game application